Arranjo e descrição do acervo documental memória acadêmica: vestígios da ditadura civil-militar na UFSM - Nascimento, Maiara de Arruda (2017)
In this study, the Academic Memory Documentary Collection, produced by the Federal University of Santa Maria (UFSM) and under the custody of the Department of General Archives (DAG) of the University, is presented. This collection, which covers the period from 1960 to 1973, refers to the initial years of the founding of UFSM, coinciding with the period of the establishment of the civil-military dictatorship in Brazil. In addition, it is composed of typologies that have not yet received documentary treatment, among them the journals of the Brazilian Studies and Problems class (EPB), a doctrinal discipline that was made compulsory during the dictatorship and whose purpose was to promote among students the homogenization of thoughts in favor of the scheme. In this sense, the objective of the research is to elaborate the descriptive instrument selective catalog for the class diaries of the discipline of EPB, in order to help in understanding how the dictatorial period occurred in the UFSM. Methodologically, the work is a case study, with a qualitative approach and using the techniques of bibliographic survey, direct observation and documentary analysis. The historical period regarding the dictatorship was studied, in order to gain a better understanding of how the events of the period reflected on institutions of higher education. It was identified the documentary situation of the Academic Memory Collection, its characteristics, typologies and research possibilities. The archival description and archival policies instituted at UFSM were analyzed. It was verified that the new policy of arrangement and description of documents of the UFSM was applied satisfactorily next to the Academic Memory Collection and to the journals of class of EPB. From the accomplishment of these steps, the final product of the master's thesis, the selective catalog of the class diaries of the discipline of EPB, was obtained. Therefore, it is hoped to contribute with the researchers of the theme of the dictatorship in Brazil, in order to help in understanding the impact of the regime in the UFSM, considering that the other documentary sources about the period were not located in the archives of the institution until the moment.